2014
DOI: 10.1016/j.nds.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of Evaluated Half-lives of Double-beta Decay

Abstract: A new evaluation of 2β-decay half lives and their systematics is presented. These data extend the previous evaluation and include the analysis of all recent measurements. The nuclear matrix elements for 2β-decay transitions in 12 nuclei have been extracted. The recommended values are compared with the large-scale shell-model, QRPA calculations, and experimental data. A T 2ν 1/2 ∼ 1/E 8 systematic trend has been observed for recommended 128,130 Te values. This trend indicates similarities for nuclear matrix el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…(Lodders et al 2009); alpha, beta and double-beta decay half lives (T 1/2 ) are gathered from the Evaluated Nuclear Structure Data File (ENSDF 2020) and Ref. (Pritychenko 2014), respectively.…”
Section: Neutron Fluence Of S-process Nucleimentioning
confidence: 99%
“…(Lodders et al 2009); alpha, beta and double-beta decay half lives (T 1/2 ) are gathered from the Evaluated Nuclear Structure Data File (ENSDF 2020) and Ref. (Pritychenko 2014), respectively.…”
Section: Neutron Fluence Of S-process Nucleimentioning
confidence: 99%
“…It is less probable than a double beta decay with the emission of two electrons and two neutrinos (2νββ). The latter process has been detected in direct experiments for 11 different nuclei [1,2], whereas there are only a few indications of the 2νECEC process which have been seen in 78 Kr. They were discussed in our previous works [3,4], and a geochemical measurement for 130 Ba [5,6] with the half-lives of the order of 10 21 years.…”
Section: Introductionmentioning
confidence: 95%
“…2 shows the Q ββ = B(A, Z + 2) − B(A, Z) + 2∆ npe value of these isotopes. Since the first experiments on 2νββ decay [19,20], a dozen of isotopes have already been measured with half-lives T 2ν 1/2 ranging from 10 18 to 10 21 years [15,21,22,23]. The 0νββ decay mode was first considered by Furry [24] who was motivated by the seminal papers of Majorana [25] and Racah [26] which suggested that the neutrino may coincide with its own anti-particle.…”
Section: Introductionmentioning
confidence: 99%